Morphometric Study of Dry Human Patella with Its Clinical Correlation - Pratima Baisakh; Lopamudra Nayak; B Shanta Kumari; Saurjya Ranjan Das (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background- Patella is the largest sesamoid bone and forms the femuro-patellar component of the knee joint. Dimensions and classification of patellae are important anthropologically as well as clinically.Aims & Objectives- Morphometry of patella has a definite role in implant design and reconstructive surgeries of knee joint. The present study aims to find out different dimensions of patella and its facets on both sides and compared.Material & Methods- The morphometric study comprised of sixty (30 left and 30 right) dry human patella collected from department museum by using sliding digital calliper. The different parameters studied are height, width, thickness of patella, length and width of medial and lateral facets. Classification of patella was done by using the measurements of its articular facets.Observations- The mean height, width, thickness of patella of left side were found to be 37.79mm, 38.26mm, 19.35mm and that of right side were 35.72mm, 34.91mm, 17.64mm respectively. The mean width of medial and lateral articular facet of left side were 19.42mm, 21.21mm and that of right side were 18.33mm,20.97mm respectively. Width of lateral articular facet is significantly larger than that of medial articular facet of same side(p<0.05) and 85% of patella belongs to Wiberg typeB.The mean patellar thickness on left and right side is 19.35mm & 17.64mm respectively,left side being significantly more than(P<0.05) that of right side.Conclusion- These dimensions of patella may be helpful for different patellofemoral operations like knee arthroplasty, ligament repair, proximal tibial osteotomy, implant design for knee replacement and for forensic measurements.